Sur la multiplicité de la première valeur propre de l'opérateur de Schrödinger avec champ magnétique sur la sphère S2 - Besson, Gérard; Colbois, Bruno; Courtois, Gilles (My University, 1998)
The purpose of this text is to study the first eigenvalue of Schrodinger operator with magnetic field on the 2-sphere and to show that its multiplicity can be arbitrarily high. We also show that this multiplicity is bounded in terms of the curvature of the corresponding connection. This answers a question asked by Y. Colin de Verdiere.